Realizing Anti-Corruption Education that Synergizes with the Five Souls of Islamic Boarding Schools - Soritua Ahmad Ramdani Harahap; Fajar Surya Ari Anggara (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: Currently, the role of Islamic boarding schools has a very significant impact on advancing education in Indonesia. Amidst the moral decline of the millennial generation and the bad behavior of corruption from bad officials, education is an important aspect that needs to be highlighted. Armed with moral and mental instillation in Islamic boarding schools, it is hoped that it will produce the next generation who are anti-corruption and carry out the mandate properly. This research method uses the literature review method by reading primary and secondary literature on anti-corruption attitudes that synergize with the five souls of Islamic boarding schools. The results of this study explain that pesantren education can produce an anti-corruption generation based on the five aspects of the five souls of pesantren, namely sincerity, simplicity, self-sufficiency, ukhuwah Islamiyyah and freedom. The principles taught at Islamic boarding schools enable them to function as a stronghold and offer resources to its graduates so they can uphold the principles they have acquired. Keywords: anti-corruption education, five souls, islamic boarding school, education.